AN INVESTIGATION INTO THE PREVALENCE AND CAUSES OF DRUG AND CHEMICAL POISONING IN PATIENTS - Vaghar, Mohammad Islami (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Oral or intravenous use of drugs in amounts higher than therapeutic doses can cause poisoning or death. This condition which is called poisoning accounts for 15–20% of referrals to emergency units. Most death cases in adults are also reported to be attributed to this condition. The present study was carried out to investigate the prevalence and causes of poisoning in patients who had referred to the emergency department of Tabriz's Sina Hospital in 2012–2013. Methods: In so doing, a cross-sectional analytic descriptive study was carried out to examine the prevalence and causes of poisoning among the patients who had referred to the poisoning ward of Sina Hospital affiliated with Tabriz University of Medical Sciences. Result: The results of the present study showed that toxicity was prevalent among 44.16% of the patients who had referred to the emergency department, and it was significantly higher among the women compared to the men. Of the studied 988 patients, 567 had used only one drug and 16 two drugs at the same time, 14 patients had abused drug and chemical materials, 80.3% of them had no history of suicide, and 49.7% were reported with poisoning with home drugs. The results also indicated no significant relationship between the type of drug and intentional poisoning. Conclusion: It could be concluded that marital and occupational status were significantly related to intentional poisoning.